Research Note: The EU Constitution and the British Public: What The Polls Tell Us About the Campaign That Never Was - Baines, Paul R.; Gill, Mark (Oxford University Press, 2006)
In Switzerland and the USA, referendums are so ubiquitous that a highly diverse industry has spawned up around them (Bowler, Donovan, & Fernandez, 1996). They are now increasingly commonplace in the EU as it enlarges. Up until June 2005, Britons expected to be asked to consent or reject the proposed EU Constitutional Treaty in a national referendum but the French and Dutch no votes in their own referendums in May and June 2005 scuppered this and Britain and other EU countries paused for a period of reflection. The ‘non’ and ‘nee’ votes constituted public defiance of their governments’ appeal to accept the EU Constitution, indicating how far removed the French and Dutch political elites were from the public (see Parker, 2005). In this research note, we consider British public opinion on Europe and the Constitutional Treaty, providing a summary of the referendum process along five key themes as follows: A sceptical view of the Constitution: All polls showed that a majority of British people intended to vote ‘no’ rather than ‘yes’ in the referendum. A persuadable electorate: More detailed analysis highlights the crucial importance of those who had not made up their minds and how they might affect the outcome of the vote. A largely under-informed public: The lack of information about Europe that the British public possessed characterizes British opinion both towards the Constitution and Europe more generally. A country that sees itself distinct from Europe: Perceived distinctiveness is important to understanding British public opinion on Europe. An unimportant event: The referendum campaigns failed to capture the imaginat